Academia?private sector collaborations in the Costa Rican Information and Communication Technology (ICT) cluster. (19th April 2010) - Ciravegna, Luciano
Costa Rica has two large public universities. They educate the workforce of the Costa Rican Information and Communication Technology (ICT) cluster, which transformed a small coffee-exporting country into the first Latin American ICT producer per capita. They also created the engineers and technicians that have attracted investments from several knowledge-intensive Multinational Corporations (MNCs), including Intel, and account for a far larger share of Research and Development (R&D) expenditure than the Latin American average. Yet, there are only three cases of collaboration between universities and the private sector. This study discusses how they emerged, their developmental effects, and questions why such collaborations are so uncommon.